Hydrophobicity of laser-textured soda-lime glass - Nur Najwa, K. A.; Hilmi, M.; Aqida, S.N.; Izwan, Ismail (IOP Publishing, 2024)
This paper studies the effect of the modified soda-lime glass surface that reduces water adhesion and raises the water contact angle by modifying the laser processing parameter. The study looked at how these variables affected the water contact angle and surface morphology. The characterization was performed using an inverted metallurgical microscope for surface morphology, and a sessile drop test setup for water contact angle measurement and bricklayer pattern with two different hatch spacings of 0.3 and 0.5 mm was used. The results revealed that the highest water contact angle achieved after surface modification for 0.3 mm was 98.97° at 1000 mm/min and 1.0 W while for 0.5 mm at 93.01°, at 600 mm/min and 1.2 W, improved its hydrophobicity from untextured glass 32.35°. Both sample patterns with 0.3 and 0.5 mm show no defect and all samples seem to have a mark from laser texturing with an increase in power, the laser mark on the surface becomes wider and the large gap between the line becomes more distinct. These findings are significant for designing hydrophobic glass surfaces using laser texturing.